Perceived benefits and barriers to the use of long-acting injectable antiretroviral treatment among adolescents and young people living with HIV in Western Kenya: qualitative findings from the KuwaFree! LiveFree! Study - Hassan, Shukri A.; Munyoro, Dennis; Maju, Mehar; Biegon, Whitney; Bakari, Salim; Kaguiri, Eunice; Jumah, Anjellah; Omollo, Mark; Obare, Valerie; Bernard, Caitlin; Apondi, Edith; Were, Edwin; et al. (Frontiers in Medicine, 2025)
IntroductionAdolescents and young people living with HIV (AYPLHIV) face significant hurdles in adhering to daily oral antiretroviral therapy (ART). Long-acting (LA) ART, such as injectable cabotegravir and rilpivirine, may help overcome these hurdles. However, little is known about the perceived benefits and barriers to LA ART usage by AYPLHIV in resource-limited settings.MethodsWe conducted focus group discussions (FGDs) with four target groups of adolescents/youth, providers, policymakers, and other advocates in western Kenya from November 2021 to April 2022. The FGDs elicited participants' thoughts on LA ART implementation in Kenya, particularly the benefits and barriers of LA ART use amongst AYPLHIV. Our analysis combined both inductive and deductive approaches, beginning with open coding of the data, then organizing them in predetermined socio-ecological model (SEM) domains.Results and discussionWe conducted a total of seven FGDs with 58 participants across four stakeholder groups: AYPLHIV (2 FGDs, n = 14), healthcare providers (2 FGDs, n = 19), health/youth advocates (2 FGDs, n = 16), and policymakers (1 FGD, n = 9). We identified several benefits, largely centered around the individual and interpersonal level, as well as barriers, largely centered around the health systems levels. Participants viewed LA ART as a welcome alternative to oral ART due to benefits like improved adherence, reduced pill burden, increased convenience, enhanced privacy, decreased stigma, lower risk of accidental disclosure, and convergence in using LA contraception. At the interpersonal level, LA ART was valued for furthering relationships, especially for AYPLHIV (e.g., dating). At the health systems level, LA ART expanded first-line treatment options. Conversely, barriers to health systems integration included conflicts with service models, increased clinic burden, supply chain issues, and waste disposal. Individual-level barriers included fears of injections, side effects, concerns about a new drug, and reduced effectiveness if mixing LA ART with oral ART.ConclusionsThe perceived benefits of LA ART for AYPLHIV, centering on individual and interpersonal levels of positive impacts, appear in tension with the anticipated barriers for health systems readiness in Kenya. While the prospect of offering LA ART is overwhelming positive, country programs will have to invest in health systems readiness before rolling out LA ART.